When are clinical trials registered? An analysis of prospective versus retrospective registration. Issue 1 (December 2016) - Harriman, Stephanie; Patel, Jigisha
Abstract Background Due to problems of publication bias and selective reporting, the ICMJE requires prospective registration of all clinical trials with an appropriate registry before the first participant is enrolled. Previous research has shown that not all clinical trials are registered at this time (prospectively). This study investigated the extent and timing of trial registration. The aims were to determine 1) the proportion of clinical trials that were registered prospectively or retrospectively and 2) when retrospective registration took place in relation to submission to the journal in which they were published. Methods All clinical trials published in theBMC series in 2013 were identified. All articles that met the study's inclusion criteria were categorised into one of three categories: 1) prospectively registered, 2) retrospectively registered before submission to the journal in which they were published or 3) retrospectively registered after submission to the journal in which they were published. Results One hundred and eight eligible studies were identified. Of these, 33 (31 %) reported studies that were registered prospectively, 72 reported studies that were registered retrospectively (67 %) and three articles (3 %) did not include a trial registration number. Of the 72 studies that were registered retrospectively, 66 (92 %) were registered before the article was submitted to the journal and six (8 %) were registered after the article was submitted to the journal. Conclusions Ten years after the ICMJE requirements for prospective registration of clinical trials this study found that the majority of included clinical trials were registered retrospectively but before submission to a journal for publication. This highlights the need for organisations other than journals, such as research institutions and grant giving bodies, to be more involved in enforcing prospective trial registration.